Remote Delivery of the Satellite Virtual Fracture Clinic - a Pilot Report of the First 500 Cases. Issue 4 (April 2021) - Hughes, Andrew J.; Moloney, Darren P.; Fraser, Caroline; Dembo, Joan; O'Brien, Louise; Corcoran, Marie; Crowley, Michelle; Conlon, Breda; Sheehan, Eoin
Highlights: The Satellite VFC allows trauma from an offsite emergency department to be managed remotely by a tertiary Orthopaedic Surgery Department. Of the 500 pilot cases, 58% were discharged directly, with a return rate of only 3.8%; saving the hospital group over €50, 000. The process is reliable, reproducible way to deliver remote specialist trauma care through virtual satellite clinics. Rural communities benefit greatly from remote access to centralised specialist decisions, whilst availing of local healthcare resources, thus obviating the need to travel excessively. The Satellite VFC is cost effective and time saving, whilst narrowing the gap between stakeholders within hospital groups. Abstract: Presenting to the fracture clinic carries economic, social and societal consequences. The virtual fracture clinic (VFC) has proven to be a safe, patient-focused, cost-effective means of delivering trauma care, whilst reducing unnecessary clinic attendances. Within our institution, a Satellite VFC was established, so as to accommodate an offsite referring emergency department. The VFC database was accessed to identify the first 500 patients who were referred to the Satellite VFC. The decision made for each patient, the rate of returns to the clinic, and the rate of referrals requiring surgical intervention, following discussion at the VFC, , were identified. A cost analysis and cost comparison was carried out between the Satellite VFC and the traditional "face to face" fracture clinic. There were 500 patients referred to the Satellite VFC within the study period. Of such patients, 288 (58%) were discharged directly following review at the Satellite VFC, 141 patients (28%) were referred to physiotherapy, 50 (10%) were redirected to the trauma clinic, 11 (2%) were sent directly to hand therapy, and 10 (2%) were sent to the ED review clinic. Patients who returned to the fracture clinic accounted for 3.8% of all referrals, and 0.2% of all referrals necessitated surgical intervention. This pilot initiative saved the Dublin Midlands Hospital Group over €50, 000. The Satellite VFC is the first of its kind in the literature. Rural communities worldwide would benefit from remote orthopaedic management of suitable fracture patterns. The true value of the Satellite VFC process comes from its use of robust patient care pathways, rationalising resource use and minimising patient travel, whilst demonstrating reliable outcomes and promoting safety.